Islamic Culture and its Historical Formation in the Territory of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the stages of formation and development of Islamic culture in Uzbekistan. The introduction of Islam into the region, its integration with local culture and traditions, and its impact on science, architecture, art, and literature are studied. The role of great thinkers and scholars in the development of Islamic civilization in the Transoxiana region is also highlighted. The article also analyzes the current state and prospects of Islamic culture in Uzbekistan based on historical sources and modern research.